Study guides

☆☆

Q: How do you factor x squared plus 3 x minus 18?

Write your answer...

Submit

Still have questions?

Related questions

(x2 + 7x - 18) = (x + 9)(x - 2)

(x + 2)(x - 9)

2222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222

A factor is like this. Original :x^2 + 7x - 18 (( x squared plus six x minus 18) Factored: (x+9)(x-2) ((x plus nine times x minus two))

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

That factors to (x - 3)(x + 6)

12 squared plus 18 squared is equal to 468.

If that's -18y2, the answer is (3x - 2y)(x + 9y)

Since the problem has 4 terms, first you factor x cubed plus 9x squared, then you factor 2x plus 18. So when you factor the first two term, you would get x sqaured (x plus 9). Then when you factor the last two terms and you get 2 (x plus 9). Ypure final answer would be (x squared plus 2)(x plus 9)

2(x - 3)(x - 3)

I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.

(x - 3)(x - 18)

2(4x - 3)(x + 3)

0 = 2m^2 - 2m + 36 0 = 2(m^2 - m + 18) 0 = m^2 - m + 18

(x - 3)(x^2 + 6)

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions: -6 plus or minus (3 times the square root of 2) x = -1.75735931288 x = -10.24264

(x, y) = (-3, -3) or (3, 3)

x2 - 9x + 18 = (x - 3)(x - 6)

b= 10

Since minus a negative is the same as a plus, then 18 - (-18) is the same as 18+18 = 36

The given expression can be simplified to: 3X squared +27

18 + 12 + 0 - 4 - 10 = 16

18

6(3r^2 - 14r + 3) and (2c + 1)(c - 9)

-18 + 25 = 7